Effectiveness of Exercise and Diet on Quality of Life among Adults with Uncontrolled Type 2 Diabetes Mellitus in Eket, Nigeria - Donatus Onyeka Adigom; Imo Emmanuel Udoh; Mary Richard Akpan (American Journal of Biomedicine and Pharmacy, 2026)
Purpose: This study evaluated the effect of exercise and diet on quality of life (QoL) among adults with uncontrolled type 2 diabetes mellitus (T2DM) in Eket Nigeria. Methods: In a four-arm randomized controlled trial,153 patients were allocated to: combined exercise and diet (n = 38), exercise-only (n =38), diet-only (n = 38), or control (n = 39) group. Interventions were delivered over 6 months. All patients were allowed to access their usual diabetes care. QoL was assessed at baseline and at follow-up. Within-group changes were analysed using the Wilcoxon signed-rank test, while between group differences were assessed using the Kruskal-Wallis H test with Bonferonni-adjusted post hoc comparisons. Effect sizes were calculated using standardized test statistics (r) and epsilon-squared (ɛ2). P-values < 0.05 were considered statistically significant. Results: The mean age, HbA1c and baseline BMI of the patients were 50 ± 15 years, 7.9 ± 1.5% and 23.88 ± 5.75 Kg/m2 respectively, and 62.7% of patients were females. At 6 months, QoL improved significantly in the exercise and diet (z = -4.910, p < 0.001, r = 0.80), exercise-only (z = -2.560, p = 0.010, r = 0.42), and diet-only groups (z = -3,022, p =0.003, r = 0.49). Between-group differences were significant (H(3) = 33.42, p < 0.001, ɛ2 = 0.204), with the combined exercise and diet intervention demonstrating the greatest clinically meaningful improvement. Conclusion: The QoL findings support integrated lifestyle intervention as an effective and clinically meaningful strategy for managing T2DM.